IMF Interactions with Member Countries. (Independent Evaluation Office Reports; Independent Evaluation Office Reports, 2010)
This report presents the findings of an evaluation of the effectiveness of IMF interactions with its member countries during the period 2001-08, with special emphasis on 2007-08. It analyzes IMF interactions with its entire membership, broken down into three main country groups: advanced economies, emerging economies, and Poverty Reduction Growth Facility (PRGF)-eligible countries. The report comes at a critical juncture for the international monetary system, when the IMF has adopted a more flexible approach to lending and been given new responsibilities, as well as a major infusion of resources to help members deal with the global financial crisis. It highlights lessons learned from the evaluation that are most relevant to the tasks that lie ahead for the IMF.